2014
DOI: 10.12890/2014_000092
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Cerebral Oedema

Abstract: Hereditary angioedema (HAE) is a rare genetic disorder transmitted as an autosomal dominant trait, characterized by reduced plasma concentration or by the presence of non-functional C1 esterase inhibitor. Oedema caused by HAE mostly affects the skin and bowel and can induce swelling of genitalia. Oedema can be life threatening if it causes swelling of the larynx with obstruction of the airways. We describe the case of a 52-year-old man who presented a neurological emergency (coma), where the remarkable localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…However, the neurovascular system affected by C1INH impairment was never examined and brain pathology was not evaluated in this knockout mouse model. It is important to note that migraines, stroke, cerebral symptoms, blindness, tetraspasticity, and other irreversible brain damage can also occur in HAE (Bonnaud et al, 2012;Bork et al, 2017;Chung & Kim, 2012;Lasek-Bal, Holecki, Handzlik-Orlik, Smertka, & Dulawa, 2015;Neri et al, 2014). Moreover, HAE patients sometimes manifest with depression and anxiety (Fouche, Saunders, & Craig, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the neurovascular system affected by C1INH impairment was never examined and brain pathology was not evaluated in this knockout mouse model. It is important to note that migraines, stroke, cerebral symptoms, blindness, tetraspasticity, and other irreversible brain damage can also occur in HAE (Bonnaud et al, 2012;Bork et al, 2017;Chung & Kim, 2012;Lasek-Bal, Holecki, Handzlik-Orlik, Smertka, & Dulawa, 2015;Neri et al, 2014). Moreover, HAE patients sometimes manifest with depression and anxiety (Fouche, Saunders, & Craig, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A 80 year old study by Crowe and co-workers linked allergy with cerebral oedema, also called cerebral allergic oedema (Crowe, 1942). Another study by Giardino and co-workers demonstrated the presence of cerebral oedema in a 52-year-old patient affected with hereditary angioedema (Giardino et al, 2014). Additionally, Tan and colleagues demonstrated the first incidence of vasogenic cerebral oedema induced by a cell-mediated hypersensitivity reaction to a nickelcontaining aneurysm clip (Tan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, for patients who have increasing edema unresponsive to steroids, there are few additional medical therapies available. is, combined with recent research that supports bradykinin's role in both tumor invasion and vasogenic edema, has led to interest in the usefulness of C1INH as a potential therapy to decrease the amount of bradykinin generated by malignant glioblastoma cells [3,4,11]. Our case discusses a patient with advanced glioblastoma who had diffuse angioedema refractory to steroid therapy who responded well to plasma-derived C1INH replacement.…”
Section: Introductionmentioning
confidence: 91%
“…e patient at this time also had significantly increased vasogenic cerebral edema seen on imaging on 2/27/2018. Despite these normal labs, it was decided to try plasma-derived C1INH due to literature suggesting potential benefits to cutaneous angioedema, cerebral vasogenic edema, and possible slowing of GBM progression [3,4,11]. e patient was thus started on 20 units/kg infusions twice weekly on 3/13/2018.…”
Section: Case Reportmentioning
confidence: 99%